Techno-humanity paintings: art as social commentary in the digital age - Luna, Charles, author; Sullivan, Patrice, advisor; Kees, Nathalie, committee member; Kokoska, Mary-Ann, committee member; Martell, Christine, committee member (Colorado State University. Libraries, 2014)
My thesis paintings utilize narrative to convey social commentary related to humanity in the Information Age. During the early part of the new millennium, I have found the social assimilation of digital media tools and systems, along with the collective beliefs and behaviors associated with them, to be both fascinating and disconcerting. Through my art I endeavor to express the paradoxical relationship between the established social benefits of information technology (IT) and its questionable effects on humanity. The work allegorically mingles the socially normalized with the absurd suggesting implicit dissonance underlying explicit harmony. The atypical integration of personal imagery with both historical and contemporary iconography is designed to evoke divergent contextual associations of the subject matter. Through these conceptual mechanisms the work encourages reflection regarding the cultural influence of IT in society.